Pemberdayaan Kader Posyandu melalui Inovasi Pentol Lele Kreasi (Pentole Kres) untuk Penanggulangan Stunting di Kelurahan Tobimeita Kota Kendari - Ainurafiq, Ainurafiq; Handriani, Indah; Anasari, Wa; Deni, Deni; Misdayanti, Misdayanti; Malik, Mayurni Firdayana; Ali, Nur Fitriana Muhammad (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aims to improve the understanding and skills of Posyandu cadres in optimizing the use of catfish as a source of nutrition through the innovation of the Pentole Kres product to overcome stunting in Tobimeita Village, Kendari City. The method of implementing this service uses community empowerment through education and training activities. The program evaluation uses pre-test and post-test instruments which are analyzed using a paired t-test. The results of the service showed an increase in participant understanding of 85%, while 100% of participants experienced an increase in practical skills, and the average skill score increased from 2.4 before training to 4.5 after training. Based on the results of this community service program, it can be concluded that the community empowerment approach utilizing local potential, such as catfish, is effective in improving the understanding and skills of Posyandu cadres in managing nutritional sources to combat stunting.